The Influence of Knowledge, Perceptions, and Preferences on Customer Behavior Through Religious as An Intervening Variable - Alfian; Amiruddin Yahya; Lisa Marzelia (IAIN Langsa, 2023)
This study analyzes the impact of knowledge, perceptions, and preferences on customer behavior through religiosity as an intervening variable at Bank Aceh Syariah Aceh Tamiang Regency. This study employs field research with a sample size of 96. The data analysis technique used is PLS-SEM version 3.0, which includes Outer Model, Inner Model, and Hypothesis Test analysis. The findings indicate that knowledge has a direct positive effect on customer behavior, and that knowledge through religiosity also has a positive and significant impact. Perception variables have a positive but insignificant effect on customer behavior, while religiosity has a positive and significant effect on perception. Preferences have a positive but insignificant effect on customer behavior, while religiosity has a negative and insignificant effect on preferences. Additionally, religiosity has a positive and significant effect on customer behavior at Bank Aceh Syariah Aceh Tamiang Regency. The implications of this research can serve as a reference for academic studies by government officials, Islamic banking practitioners, and the wider community to support scientific development, products, and technology in the future development of Islamic banks. Further research should consider additional and intervening variables for maximum results.